Clinical manifestation of autosomal dominant hyper-IgE syndrome with associated autism - Muciek, Adrianna; Rutkowska-Zapała, Magdalena; Szaflarska, Anna (Alergologia Polska - Polish Journal of Allergology, 2025)
Autosomal dominant hyper-IgE syndrome (AD-HIES) is a rare inborn error of immunity that affects multiple organs and presents a wide array of clinical features. The disease is caused by a mutation in the STAT3 gene, which results in disruption of both innate and adaptive immune responses. This manifests as elevated IgE levels, recurrent bacterial and fungal infections, eczema, and the presence of “cold” abscesses, primarily caused by Staphylococcus aureus . The non-immunological symptoms of AD-HIES include facial dysmorphia, craniosynostosis, retained childhood dentition, hyperextensibility, scoliosis, and vascular abnormalities. This report presents a case of hyper-IgE syndrome, confirmed by molecular test, accompanied by autism spectrum disorder.